Ectodermal Dysplasia: A Genetic Review - Deshmukh, Seema (Jaypee Brothers Medical Publishers, 2012)
Ectodermal dysplasia is a rare hereditary disorder with a characteristic physiognomy. It is a genetic disorder affecting the development or function of the teeth, hair, nails and sweat glands. Depending on the particular syndrome ectodermal dysplasia can also affect the skin, the lens or retina of the eye, parts of the inner ear, the development of fingers and toes, the nerves and other parts of the body. Each syndrome usually involves a different combination of symptoms, which can range from mild to severe. The history and lessons learned from hypohidrotic ectodermal dysplasia (HED) may serve as an example for unraveling of the cause and pathogenesis of other ectodermal dysplasia syndromes by demonstrating that phenotypically identical syndromes can be caused by mutations in different genes (EDA, EDAR, EDARADD), that mutations in the same gene can lead to different phenotypes and that mutations in the genes further downstream in the same signaling pathway (NEMO) may modify the phenotype quite profoundly. The aim of this paper is to describe and discuss the etiology, genetic review, clinical manifestations and treatment options of this hereditary disorder. How to cite this article: Deshmukh S, Prashanth S. Ectodermal Dysplasia: A Genetic Review. Int J Clin Pediatr Dent 2012; 5(3):197-202.